PENAHANAN DAN PENANGGUHAN PENAHANAN DALAM TEORI DAN PRAKTEK - Thomas Abbon (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Abstract The issue of upholding the rule of law is a chore that must be resolved by the current government. The state and nation have been disadvantaged from all aspects, because in the end the harassment of the law has given rise to corruption, collusion and nepotism. One of the things that stands out about law enforcement is the issue of detention and suspension of detention and sentencing that has to do with detention. The problem of detention and the detention in practice so far has been widely distorted by unscrupulous law enforcers and this institution has become an